Modelling the effect of oxygen concentration on bacterial growth rates. (February 2019) - Couvert, Olivier; Divanac'h, Marie-Laure; Lochardet, Anne; Thuault, Dominique; Huchet, Véronique
Abstract: Predicting the microbial safety of food products stored in modified atmosphere packaging implies taking into account the effect of oxygen reduction on microbial growth. According to their respiratory-type, the micro-organisms are not impacted similarly by the oxygen concentration. The aim of this article was to quantify and model the oxygen effect on the growth rates of 5 bacterial species: Listeria monocytogenes and Bacillus weihenstephanensis (facultative anaerobic), Pseudomonas fluorescens (strict aerobic), Clostridium perfringens and Clostridium sporogenes (strict anaerobic). The results showed the oxygen concentration doesn't modify the behavior of both facultative anaerobic strains. The growth rate of P. fluorescens decreased with the oxygen concentration, but the effect is only noticeable when the oxygen concentration fell below 3% in the gaseous phase. Conversely, the oxygen acted as a growth inhibitor for both Clostridium species. But total inhibition is reached only for 3.26% and 6.61% respectively for C. sporogenes and C. perfringens . Two models have been fitted for both respiratory-types, the first is the Monod model considering oxygen as a substrate for growth, and the second is the classic inhibitory model based on minimal inhibitory concentration. Highlights: C. perfringens and C. sporogenes tolerate low oxygen presence for growth. P. fluorescens can grow with oxygen as low as 0.1%. L. monocytogenes and B. weihenstephanensis growth is unaffected by the low oxygen level. The inhibitory model describes the behavior of both Clostridii in the presence of oxygen. Oxygen is a limiting nutrient for P. fluorescens ; this is described by the Monod model.